Evaluation of BER for the EHF Communication System Serving Sharp-Coned Reentry Vehicles - Yang, Xiaocui; Yuan, Kai; Wang, Yuhao; Liu, Yiwen (Frontiers in Earth Science, 2022)
“Communication blackout” could lead to severe risks to reentry vehicles. Previous studies have shown that EHF (extremely high frequency) communication is a potential solution to the “communications blackout” and was mostly used for blunt-coned vehicles. EHF communication with sharp-coned vehicles was rarely concerned before. In the present study, the propagation characteristics of the modulated EHF signals in a time-varying plasma sheath covering sharp-coned vehicles were studied numerically. The plasma sheath was obtained by solving a hypersonic fluid dynamics model. The signals propagation model is developed based on geometric optical theories. The carrier frequencies concerned in the present study are the “atmospheric window” frequencies, which are 94, 140, and 225 GHz, respectively. Based on the signal propagation characteristics, the EHF communication system was modeled. The modulation modes concerned in the present study are the 2ASK, 2PSK, and 2FSK, respectively. The results show that 1) the transmission coefficient of EHF signals in the side channel of the plasma sheath of the sharp-coned reentry vehicle increases with carrier frequency, 2) the gap between different channels at specific carrier frequency decreases with time, 3) the phase shift tends to be stable as the carrier frequency increases, and 4) the bit error rate (BER) varies with time and is affected by the location of the onboard antenna, carrier frequency, and modulation mode. The study shows that, in order to achieve good BER performance for the EHF communication system, 2PSK modulation of the signal at 140 GHz is recommended, and the onboard antenna is suggested to be installed on the wall and close to the bottom of the sharp-coned vehicle.